Anticancer efficacy of magnetite nanoparticles synthesized using aqueous extract of brown seaweed Rosenvingea intricata, South Andaman, India - V. Swathi Pon Sakthi Sri; Y. Aron Santhosh Kumar; M. Savurirajan; Dilip Kumar Jha; N. V. Vinithkumar; G. Dharani (Scientific Reports, 2024)
Abstract Cancer is a global issue and hence various efforts are being made. Iron oxide is considered a significant biochemical agent in the biomedical arena for cancer treatment. Marine macroalgae-mediated iron oxides especially, magnetite (Fe3O4) nanoparticles (NPs) are a prospective alternative to diagnose and treat cancer owing to their fluorescent and magnetic properties. We intend to appraise the usability of the aqueous extract of Rosenvingea intricata (R. intricata) in Fe3O4 NPs synthesis and to study their cytotoxic effects against human hepatocarcinoma (Hep3B) and pancreatic (PANC1) cancer cells. In the present study, R. intricata were collected from the coastal region of South Andaman, India. Aqueous extracts of R. intricata were utilized to synthesize Fe3O4 NPs via the co-precipitation method. Phycosynthesized Fe3O4 NPs exhibited wide peak at 400–600 nm from ultraviolet–visible diffused reflectance spectroscopic analysis which validated the formation of NPs. Band edge emission peak at 660 nm in fluorescent spectra confirmed the quantum confinement in Fe3O4 NPs. Fourier transform infrared spectroscopy confirmed the role of R. intricata as a capping and reducing agent with functional groups such as O–H, C–H, C=O, N=O, C=C, C–O, C–N, and C–S arising from amino acids, polysaccharides, aliphatic hydrocarbons, esters, amides, lignins, alkanes, aliphatic amines, and sulfates. Physicochemical properties such as crystallite size (14.36 nm), hydrodynamic size (84.6 nm), irregular morphology, elemental composition, particle size (125 nm), crystallinity, and saturation magnetization (0.90007 emu/g) were obtained from x-ray diffractometer, dynamic light scattering, scanning electron microscopy, energy dispersive x-ray spectrometer, high-resolution transmission electron microscopy, selected area electron diffraction and vibrating sample magnetometer techniques, respectively. The cell viability showed dose-dependent cytotoxic effects and enhanced the apoptosis against Hep3B and PANC1 cancer cells. R. intricata extract capped Fe3O4 NPs could be the most appropriate and effective nanomaterial for cancer treatment and management.